Veil of night : a novel - Howard, Linda, 1950- (Ballantine Books, 2010)
"Jaclyn Wilde is a wedding planner who loves her job, but working with bridezilla Carrie Edwards has been a nightmare. When Carrie is brutally murdered, everyone involved with the ceremony is under suspicion. Detective Eric Wilder finds that there's too much evidence pointing toward too many suspects. Compounding his problems is Jaclyn, with whom he shared one deeply passionate night before Carrie's death. As the heat intensifies between Eric and Jaclyn, a murderer moves dangerously close. This time the target is not a bride but a wedding planner, unaware of a killer's vow"--Book jacket.